Implications of a Sugar Tax in New Zealand: Incidence and Effectiveness - Alasdair Gardiner (New Zealand Government, The Treasury, 2016)
This paper has two aims. First, it surveys some of the literature on the likely effectiveness of sugar taxes as a policy instrument for reducing morbidity and mortality associated with obesity. There is a wide range of estimates among the literature of the price elasticity of demand for sugary products. A plurality of studies found that groups most at risk from obesity have greater price sensitivity. Studies also found there is a risk of consumers substituting unhealthy but non-taxed products for taxed products, negating any potential health improvements from a tax. The paper's second aim is to build on the literature review by analysing the possible incidence of a sugar tax in New Zealand, based on New Zealand household expenditure data. The empirical analysis presented is consistent with international evidence that a sugar tax would be regressive at the general population level.
Keywords: H2; H3; 330; Sugar sweetened beverages; tax progressivity; Zucker; Steuer; Steuerinzidenz; Körpergewicht; Sterblichkeit; Preiselastizität; Neuseeland